A Model to Measure Brand Loyalty at Private Higher Education Institutions in South Africa - Paltooram, Calvin; Bisschoff, Christo; Botha, Christoff (International Review of Management and Marketing, 2026)
The business environment for private higher education is highly competitive. Brand loyalty is one possible competitive strategy. This study aims to validate a theoretical model to measure brand loyalty and, in the process, provide a model that can be applied to measure brand loyalty of private higher education institutions. The quantitative research design collected data using a 5-point Likert-scale questionnaire from 399 alumni of private higher education institutions in South Africa. (376 thereof were usable). The results show that although the data are somewhat negatively skewed and exhibit leptokurtic kurtosis, these deviations remain within acceptable norms. Exploratory factor analyses validate the measuring criteria for each respective antecedent. The empirical findings demonstrate that customer satisfaction, service quality, brand trust, brand image, perceived value, customer relationships, dependability and reliability, technology, waiting time, switching costs, and brand involvement show strong, statistically significant positive relationships with brand loyalty. These results support the proposed theoretical model. Although the study is valuable to future researchers, its core value lies in managerial application. Management can apply the validated brand loyalty model to measure alumni brand loyalty and, furthermore, determine the influence of each brand loyalty antecedent.